Measurement of cemented carbide-PCD microdrill geometry error based on computer vision algorithm. (January 2022) - Jaini, Siti Nurfadilah Binti; Lee, Deug-Woo; Kim, Kang-Seok; Lee, Seung-Jun
Graphical abstract: Highlights: Cemented carbide-PCD microdrills were fabricated through brazing technique. Average axial straightness error of both microdrills were less than 2 μ  m. Radial runout measured at tool tip was greater than the measurement at drill body. Standard deviation and repeatability of measurements were ± 0.6 μ m and ± 1.3 μ m . Abstract: Microdrill machining is in high demand and is widely applied in various industries where the structural design and material properties of the microdrill are critical components in machining. A composite microdrill composed of cemented carbide and polycrystalline diamond balances the wear resistance, toughness, and hardness properties of the cutting tool. Nevertheless, the tool geometry error must be examined because of complex technique involved in the tool fabrication process. The investigated microdrill is fabricated through a brazing technique that connects the shank and drill body of different material compositions. A computer vision algorithm was developed specifically for measuring the axial straightness error and radial runout of the microdrill. Accordingly, the ability of the developed measurement techniques to perform precise and accurate tool geometry error measurements is evaluated in this study.